The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1177/107327480100800403
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Stage I and II Non-Small-Cell Lung Cancer

Abstract: Staging bias may affect the overall low survival of early-stage NSCLC. However, true stage-specific survival may improve with newer imaging modalities. Future advances, including closed transthoracic radiation, thermal ablative therapy techniques, and gene therapy, may supplant the need to surgically resect these tumors to achieve local control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 48 publications
0
18
0
2
Order By: Relevance
“…4,5 It is known that stage-adapted therapy significantly improved the survival of patients with cancer. 6,7 In this regard, conventional CT and MRI, mainly providing anatomical information, are performed to assess staging site of NPC, especially for the primary site and localregional metastases. However, owing to the lack of functional information, these modalities are limited in assessment of disease aggressiveness and distant metastases.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 It is known that stage-adapted therapy significantly improved the survival of patients with cancer. 6,7 In this regard, conventional CT and MRI, mainly providing anatomical information, are performed to assess staging site of NPC, especially for the primary site and localregional metastases. However, owing to the lack of functional information, these modalities are limited in assessment of disease aggressiveness and distant metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation therapy does little to improve this survival rate; even with radiation therapy, patients with stage I cancer have a median survival of only 16-25 months [2,3,22]. But, to achieve an adequate resection of a lung cancer, do we have to accept the high risks of thoracotomy?…”
Section: Discussionmentioning
confidence: 99%
“…In the early 1990s, some investigators claimed that VATS surgery was technically too difficult and that an adequate lymph node dissection was not possible [22]. Since that time, however, several authors have reported that VATS lobectomy with lymph node dissection is technically feasible [13,14,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 150 factors that help determine NSCLC prognosis, the tumor stage, as defined by the American Joint Committee on Cancer is considered to be the most important [2,3]. Thus, the choice of therapy options, including surgery, radiation therapy, and chemotherapy-used alone or in combination [4,5]-is based on the tumor stage. Consequently, the accurate determination of tumor size, potential infiltration of adjacent structures, mediastinal lymph node involvement, and the detection of distant metastases are of central importance.…”
mentioning
confidence: 99%